Ionic Liquid Electrolytes with Various Constituent Ions for Graphene-based Supercapacitors. (10th April 2015) - Huang, Po-Ling; Luo, Xu-Feng; Peng, You-Yu; Pu, Nen-Wen; Ger, Ming-Der; Yang, Cheng-Hsien; Wu, Tzi-Yi; Chang, Jeng-Kuei
Highlights: GNS electrode outperforms AC electrode in ionic liquid (IL) electrolyte. Constituent ions of ILs determine the capacitive performance of the GNS electrode. BMP-DCA IL is a promising electrolyte for GNS-based supercapacitors. The GNS cell shows energy and power densities of 103 Wh kg −1 and 43.3 kW kg −1 at 60 °C. Above performance is much higher than that of a cell with traditional electrolyte. Abstract: Although activated carbon shows a higher maximum capacitance than that of graphene nanosheets (GNSs) in a conventional organic electrolyte, the latter material, characterized by high conductivity and a unique planar structure, is more suitable for use in an ionic liquid (IL) electrolyte for supercapacitors. IL electrolytes consisting of various cations (1-ethyl-3-methylimidazolium (EMI + ) and N-butyl-N-methylpyrrolidinium (BMP + )) and anions (bis(trifluoromethylsulfony) imide (TFSI − ), tetrafluoroborate (BF4 − ), and dicyanamide (DCA − )) are systematically studied. Among them, BMP-DCA IL is found to be the superior electrolyte, in which the GNS electrode exhibits a capacitance of 235 F g −1 and a satisfactory rate capability within a potential range of 3.3 V at 25 °C. This electrolyte is even more promising for elevated-temperature applications. At 60 °C, a symmetric-electrode GNS supercapacitor with BMP-DCA IL is able to deliver maximum energy and power densities of 103 Wh kg −1 and 43.3 kW kg −1 (based on the active material on both electrodes), respectively, which are much higher than 19 Wh kg −1 and 17.6 kW kg −1 for a control cell with a conventional organic electrolyte.